Treatment for Mycobacterium avium complex lung disease - Sheng-Wei Pan; Chin-Chung Shu; Jia-Yih Feng; Wei-Juin Su (Journal of the Formosan Medical Association, 2020)
Mycobacterium avium complex (MAC) is the major pathologic nontuberculous mycobacteria causing lung disease (LD) in humans worldwide. Although the burden of MAC-LD has increased over the past two decades, treatment remains difficult because of intolerance of long-term antibiotics, lack of adherence to guidelines, and disease recurrence. The current guidelines recommend antibiotic initiation for patients with MAC-LD and severe disease and in those with disease progression. Thus, physicians should consider antibiotic treatment for patients with MAC-LD and cavitary pulmonary lesions or symptomatic non-cavitary nodular bronchiectasis pattern at initial visits and also for those with clinical deterioration during follow-up. The standard three-drug regimen should be macrolide, rifamycin, and ethambutol. Physicians should monitor side effects in patients and maintain the regimen for 12 months, beginning from when sputum conversion has been obtained. With adherence to guideline-based therapy, treatment is successful in two thirds of treatment-naïve patients without macrolide resistance. Without adherence, macrolide resistance can occur, which leads to poor outcomes in patients with MAC-LD. Although the discovery of new treatment options is warranted, adherence to guidelines remains most crucial in treating patients with MAC-LD. It is worth mentioning that the majority of current recommendations are based on observational studies or small-scale clinical trials.